Toma de Aquino: In libros Aristotelis De caelo et mundo expositio / Desăvârșirea sintezei aristotelice (Verbum. Revista de teologie catolică, 2025)
This paper explores Thomas Aquinas’ commentary on Aristotle’s De caelo et mundo as the culmination of his lifelong project to synthesize Aristotelian natural philosophy with Christian theology. Focusing on Books I–III, it analyses key cosmological themes such as the incorruptibility and motion of celestial bodies, the composition and transformation of sublunary elements, and the teleological order of the cosmos. Aquinas integrates Aristotelian concepts—like ether, potentiality and actuality, and natural motion—into his metaphysical and theological framework. He harmonizes Aristotle’s eternal cosmos with Christian doctrines of creation ex nihilo and divine providence, demonstrating the compatibility of reason and faith. His commentary affirms a hierarchical and purposive universe, reflecting the wisdom and care of the Creator. By uniting natural philosophy, metaphysics, and theology, Aquinas elevates Aristoteliancosmology to a theological plane, building a bridge between ancient philosophy and medieval Christianity. This study positions De caelo et mundo as the final and essential element of Aquinas’ intellectual synthesis and underscores its enduring relevance for contemporary philosophical and theological inquiry.
Keywords: Aristotelian cosmology; Scholastic philosophy; Thomistic metaphysics; Aristotelian- Thomistic synthesis; Aquinas and contemporary science